Efektivitas Penggunaan Worksheet R Dalam Pembelajaran Teori Probabilitas - Joko Sungkono; Andhika Ayu Wulandari (Universitas Veteran Bangun Nusantara, 2021)
Experiments that are often used to understand the theory of probability include the toss of currency, rolling of the dice, taking the ball randomly from a box, and drawing a bridge card. If this series of experiments is carried out several times, identifying possible samples produced is not an easy task. Learning probability theory material requires a new breakthrough in order to make it easier for students to understand according to their era. This research applies the use of R-based student worksheets (R worksheets) in learning probability theory. This paper discusses the effectiveness of using the R worksheet in learning probability theory. This research involved the experimental class and the control class. The experimental class used students in the Mathematics Statistics I course for Mathematics Education Study Program, Widya Dharma University, Klaten, while the control class used students in the Mathematics Statistics I course for Mathematics Education Study Program, Bangun Nusantara University, Sukoharjo. The experimental class used the R worksheet with R software-based learning, while the control class used the conventional method. From the pre-test result data, it is known that the 2 sample classes have the same initial ability. Based on the data analysis of the post-test scores, it is known that the experimental class scores are better than the control class. This means that the use of the R worksheet is effective in learning probability theory.